Flexible model specification and application for service-oriented software. (April 2019) - Sun, Fuyu; Zhou, Jianping; Guo, Shuai; Li, Yi
Service-Oriented Architecture (SOA) has gained considerable popularity for the development of large-scale distributed software systems. The SOA paradigm promotes the reusability and integrability of software in heterogeneous environments by means of open standards. The existing problem is that every service-oriented software development project often requires a customized development process that provides specific service-oriented software in support of requirements unique to that project. To resolve this problem, this study proposes universal service-oriented software (USOS). USOS focuses on the general simulation technology and integrates many features, which are necessary to build a correct and efficient simulation system. It is aimed at providing a professional environment to reduce the cost of modeling as well as the execution time of the simulation for multi-type models. USOS supports many advanced features such as dynamic model template generation, multi-formalism model debugging, flexible model-driven application, etc. Developers may use USOS as an open framework to build, store, and verify models very efficiently. Based on USOS, we have developed a large-scale parallel simulation platform called SIM, which is oriented to test parallel and distributed architectures, and applications in the aerospace domain. This study introduces the distinctive features of USOS for practical implementation of SIM and validates the performance by a prototype system simulation.